2007
DOI: 10.1002/cbdv.200790157
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Amide Hydrolase: From Characterization to Therapeutics

Abstract: Fatty acid amide hydrolase (FAAH) is an integral membrane enzyme within the amidase-signature family that terminates the action of several endogenous lipid messengers, including oleamide and the endocannabinoid anandamide. The hydrolysis of such messengers leads to molecules devoid of biological activity, and, therefore, modulates a number of neurobehavioral processes in mammals, including pain, sleep, feeding, and locomotor activity. Investigations into the structure and function of FAAH, its biological and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 103 publications
0
44
0
1
Order By: Relevance
“…[12,13,109,110] for recent reviews). Potential drug targets include the enzymes involved in fatty acid amide biosynthesis and degradation [111,112], transporters responsible for moving the fatty acid amides across the cell membranes [110], and analogs of the fatty acid amides themselves as agonists or antagonists for their respective receptors (Table 2) [13,113]. As detailed by Felder et al [110], the potential existence of specific transporters for anandamide and the other fatty acid amides is controversial, but accumulating evidence suggests that the simple passive diffusion of the these hydrophobic compounds across the membrane driven by FAAH-hydrolysis is insufficient to account for published anandamide uptake data.…”
Section: Pharmacological Importance Of the Fatty Acid Amidesmentioning
confidence: 99%
“…[12,13,109,110] for recent reviews). Potential drug targets include the enzymes involved in fatty acid amide biosynthesis and degradation [111,112], transporters responsible for moving the fatty acid amides across the cell membranes [110], and analogs of the fatty acid amides themselves as agonists or antagonists for their respective receptors (Table 2) [13,113]. As detailed by Felder et al [110], the potential existence of specific transporters for anandamide and the other fatty acid amides is controversial, but accumulating evidence suggests that the simple passive diffusion of the these hydrophobic compounds across the membrane driven by FAAH-hydrolysis is insufficient to account for published anandamide uptake data.…”
Section: Pharmacological Importance Of the Fatty Acid Amidesmentioning
confidence: 99%
“…1 FAAH has a relatively wide substrate selectivity, as it also catalyzes the hydrolysis of other fatty acid ethanolamides (FAE)s including oleoylethanolamide (OEA) and palmitoylethanolamide (PEA), which are agonists of the peroxisome proliferator-activated receptor (PPAR) subtype alpha. 2 Multiple studies have shown that inactivation of FAAH by active-site directed inhibitors significantly increases the level of FAEs in vivo, leading to analgesic, anti-anxiety and anti-inflammatory effects, 3 without producing the unwanted side effects observed with direct CB 1 agonists, including hypothermia, cognitive and motor dysfunctions. 4 FAAH inhibition therefore represents an attractive therapeutic strategy for the treatment of several central nervous system disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this goal, two principal endocannabinoid enzymes, fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MGL), are promising candidates for drug discovery, by modulating the effects of the two principal endocannabinoids, anandamide (AEA) and 2-arachidonylglycerol (2-AG), respectively, at the cannabinoid receptors 1 and 2 (CB1 and CB2) [4], [5]. Other important bioactive fatty acid amides, such as N -palmitoylethanolamine (PEA), N -oleoylethanolamine (OEA) and oleamide (OA), with no or very low affinity for the cannabinoid receptors, are potential substrates in FAAH and N -acylethanolamine-hydrolyzing acid amidase (NAAA) regulated metabolism.…”
Section: Introductionmentioning
confidence: 99%